Plato’s Lysis and the Erotics of Philia - Roochnik, David (Revista Archai, 2023)
This paper argues that the account of friendship (philia) present in Plato's dialogue the Lysis is rife with the disruptive and maddening force of eros.By its end it is no longer clear whether the familiar sorts of personal relationships that we typically count as friendships, and which Aristotle discusses with great sensitivity and appreciation in theNicomachean Ethics,can be meaningfully sustained. To support this thesis, the paper analyzes each of the seven, relatively self-contained arguments Socrates offers. In addition, it shows how the dramatic context in which these arguments are embedded foreshadows the dialogue's principal objective: to blur the distinction between philiaand eros by allowing the latter to infect the former